2016
DOI: 10.1177/0954405415604121
|View full text |Cite
|
Sign up to set email alerts
|

Hole-flange forming of high-strength steel sheet using one-step hot stamping-forging method

Abstract: A process of one-step hot stamping-forging for increasing the tensile strength of the hole-flanging of the high-strength steel sheets with flange thickening was developed. In this proposed method, the high-strength steel sheet is directly formed within the designed die, which is simultaneously accompanied with a resistance heating, a hole punching, and the flanging and forging processes. The electrode material is SKD61. This material is not only used as the forming of the high-strength steel sheet but also dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Then HERs of holes under different damage values in the range of 1%-10% for both materials could be obtained with the help of EFSR values in Figure 7. The method to obtain the HERs under given damage value in this study is shown in equation (15) …”
Section: Results Of Experiments and Comparison With Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then HERs of holes under different damage values in the range of 1%-10% for both materials could be obtained with the help of EFSR values in Figure 7. The method to obtain the HERs under given damage value in this study is shown in equation (15) …”
Section: Results Of Experiments and Comparison With Simulationsmentioning
confidence: 99%
“…Butcher et al 14 found that surface roughness and void initiation due to the shearing process were not significant factors on the edge cracking of baron steel used in hot stamping applications. Cheng 15 developed a one-step hot stamping–forging method to increase the tensile strength of high-strength steel.…”
Section: Introductionmentioning
confidence: 99%
“…For a more precise control of the final product hardness, the applied method for heating of the blank with the pre-hole needs to be adapted. A targeted use of several electrodes similar to Mori et al [25], or hot cutting in same stroke with hot hole-flanging comparable to Cheng [13], is conceivable. The latter allows a blank with a constant cross-section to be heated.…”
Section: Control Of Product Propertiesmentioning
confidence: 99%
“…Motaman et al [12] improved the expansion ratio during laser-assisted warm (~250 °C to 400 °C) hole-flanging of DP1000 sheet material in a progressive-die by taking advantage of dynamic strain aging. Cheng [13] developed a onestep hot stamping-forging method that enables the hole-flanging of high strength quenchable steel sheet 15B22. Despite the ongoing research, a control-oriented analysis of the relationships between the product properties and the process parameters during hot holeflanging with simultaneous heat treatment is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Hot hole flanging operations have been conducted on AHSS because of their low stretch flange ability at room temperature. Cheng [8] performed one-step hot stamping to form flanges from high strength steel 15B22. The tensile strength and breaking toughness of the formed flanges increased by 7.4% and 33% compared to flanges formed by the cold working process.…”
Section: Introductionmentioning
confidence: 99%